Calcium oxalate crystals in Conyza canadensis (L.) Cronq. and Conyza bonariensis (L.) Cronq. (Asteraceae: Astereae) - Meric, Ciler (Acta Biologica Szegediensis, 2008)
Calcium oxalate crystals (CaOx) are found in most organs and tissues of many plant species. In this study the morphology and distribution of CaOx crystals in Conyza canadensis (L.) Cronq. and Conyza bonariensis (L.) Cronq. belonging to Asteraceae were investigated. CaOx crystals display a similar distribution in organs and tissues of C. canadensis and C. bonariensis. For the identification of CaOx crystals a histochemical technique (using silver nitrate and rubeanic acid) was applied to the cleared organs and tissues. Crystals in cleared organs and tissues were viewed using an Olympus photomicroscope fitted with polarizing filters. The sample tissues were also investigated with a scanning electron microscope. CaOx crystals were found in stems, leaves, petals, ovaries, and styles of two species, but no crystals were observed in filament or other tissues. Druses were observed in the stem epidermis and cortex cells and leaf epidermis cells and mesophyll layers in both species. They were also determined in corolla and style cells. The pith parenchyma cells of stem had needle-shaped and bipyramidal crystals. Styloid crystals were present in the ovary of both species. Raphides were not observed in both taxa. This study provides additional information about the presence of CaOx crystals in Asteraceae.